2016
DOI: 10.1039/c5ra22420a
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer-based electrolyte membranes from chitosan incorporated with montmorillonite-crosslinked GPTMS for direct methanol fuel cells

Abstract: A composite membrane was fabricated from biopolymer chitosan and montmorillonite (MMT) filler as an alternative membrane electrolyte for direct methanol fuel cell (DMFC) application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…For excellent PEM that can be applied to PEMFCs, high proton conductivity and low permeability are required simultaneously. The overall balance of the membrane can be evaluated by the selectivity factor (the ratio of conductivity and methanol permeability) . As shown in Figure (b), the composite membranes show higher selectivity than that of Nafion 115, owing to the relatively higher conductivity and lower methanol permeability, indicating that doping with SZrO 2 can apparently promote the overall performance of membranes, especially at low SZrO 2 loading, that is, 0.5–1.5 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…For excellent PEM that can be applied to PEMFCs, high proton conductivity and low permeability are required simultaneously. The overall balance of the membrane can be evaluated by the selectivity factor (the ratio of conductivity and methanol permeability) . As shown in Figure (b), the composite membranes show higher selectivity than that of Nafion 115, owing to the relatively higher conductivity and lower methanol permeability, indicating that doping with SZrO 2 can apparently promote the overall performance of membranes, especially at low SZrO 2 loading, that is, 0.5–1.5 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…From table 2, the permeability decrease as more fly ash were added. It has been suggested that, this phenomenon is might due to the existence of filler which increases the tightness of composite membrane so it can suppress the methanol movement [8] . The addition of fly ash would make the membrane more difficult for solution to breakthrough as the grains made formation and covered the pore.…”
Section: Methanol Permeability Studymentioning
confidence: 99%
“…After quickly wiping off the water adhered to the surface of the membranes, the weight and dimension of wet membranes were measured. The water uptake and swelling ratio could be determined according to the following equation 1 and 2 [18] :…”
Section: Water Uptake and Swelling Ratiomentioning
confidence: 99%
“…Samples from compartment B were taken out every 30 minutes for 6 hours to determine its methanol concentration using high-performance liquid chromatography (HPLC). The methanol permeability values were determined by using equation 4 [18].…”
Section: Methanol Permeability and Proton Conductivitymentioning
confidence: 99%
See 1 more Smart Citation